Critical Failure Analysis of Superheater Tubes of Coal-Based Boiler - Kumar Gupta, Gagan (Strojniški vestnik, 2017)
This paper highlights a methodology for failure investigation of superheater tubes made of the material T-22 of a coal-based boiler. The process includes visual observation, the identification of sampling locations, the determination of the bulk chemical composition of the base alloy, microstructural investigation using optical microscopy, the exploration of finer structural details using a scanning electron microscope (SEM), the evaluation of hardness over samples obtained from different locations, the fractographic analysis of different failed locations, the X-ray diffraction (XRD) study of corrosion products adhered to inner surfaces, and the determination of the nature of the failure. Within a span of four months, three successive failures of superheater tubes were reported. The tubes were observed to have undergone significant wall thinning. Microscopic examinations using SEM on the failed region and a region some distance away on the as-received tubes were conducted in order to determine the failure mechanism. Layer-wise oxidation corrosion (exfoliation) in the inner surface was observed. Apart from major cracking, a number of nearly straight line crackings were observed in the longitudinal direction of both tubes. Close to cracking/bulging, void formation/de-cohesion of grain boundary indicated creep deformation under service exploitation. The failure mechanism was identified to be a result of excessive oxidation corrosion along the inside wall to reduce thickness, the spheroidization of alloy carbides and the coarsening of precipitate as well as creep void formation along grain boundary leading to inter-granular cracking with material flow near regions covered with thick scales. Moreover, there was a drastic reduction in bulk hardness of alloy and finally "thin lip fish mouth" fractures.
Keywords: cev pregrevalnika; fraktografska analiza; korozija; kotel na premog; lezenje; SEM; XRD